Statins and postmenopausal breast cancer risk; results from the KARMA cohort - Marie Klintman; Ann H. Rosendahl; Benjamin R. Johannesen; Deirdre Cronin-Fenton; Mikael Eriksson; Kamila Czene; Per Hall; Signe Borgquist (Cancer Causes & Control, 2026)
Purpose To study the incidence and subtype of breast cancer in relation to incident and prevalent statin use in a contemporary Swedish prospective cohort, The Karolinska Mammography Project for Risk Prediction of Breast Cancer, KARMA. Methods A total of 35,315 postmenopausal women attending mammography and included in the KARMA cohort (Jan 2011–March 2013) with data on statin use and potential confounders were studied. During eight years of follow-up, 785 incident invasive breast cancer cases were identified. Results A total of 16% of women were prevalent statin users (prior to study inclusion) and 9% were incident statin users (following study inclusion). In multivariable Cox regression analyses, there was no significant association between incident or prevalent statin use and risk of incident breast cancer (HR adj 1.24, 95% CI 0.89–1.72, and HR adj 0.90, 95% CI 0.73–1.11, respectively). Similarly, no significant association was found for incident or prevalent statin use and subtype-specific risk of breast cancer. Conclusion This prospective population-based study performed in a modern screening population with a substantial number of statin users, concurs with previous publications showing no evidence of an association between statin use and risk of postmenopausal breast cancer.

Mammographic density as an image-based biomarker of therapy response in neoadjuvant-treated breast cancer patients - Ida Skarping; Daniel Förnvik; Uffe Heide-Jørgensen; Hanna Sartor; Per Hall; Sophia Zackrisson; Signe Borgquist (Cancer Causes & Control, 2021)
Purpose Personalized cancer treatment requires predictive biomarkers, including image-based biomarkers. Breast cancer (BC) patients receiving neoadjuvant chemotherapy (NACT) are in a clinically vulnerable situation with the tumor present. This study investigated whether mammographic density (MD), assessed pre-NACT, is predictive of pathological complete response (pCR). Methods A total of 495 BC patients receiving NACT in Sweden 2005–2019 were included, merged from two different cohorts. Cohort 1 was retrospectively collected ( n = 295) and cohort 2 was prospectively collected ( n = 200). Mammograms were scored for MD pre-NACT according to the Breast Imaging-Reporting and Data System (BI-RADS), 5th Edition. The association between MD and accomplishing pCR post-NACT was analyzed using logistic regression models—for the whole cohort, stratified by menopausal status, and in different St. Gallen surrogate subtypes. Results In comparison to patients with low MD (BI-RADS a), the multivariable-adjusted odds ratio (OR) of accomplishing pCR following NACT was on a descending scale: 0.62 (95% confidence interval (CI) 0.24–1.57), 0.38 (95% CI 0.14–1.02), and 0.32 (95% CI 0.09–1.08) for BI-RADS b, c, and d, respectively. For premenopausal patients selectively, the corresponding point estimates were lower, although wider CIs: 0.31 (95% CI 0.06–1.62), 0.24 (95% CI 0.04–1.27), and 0.13 (95% CI 0.02–0.88). Subgroup analyses based on BC subtypes resulted in imprecise estimates, i.e., wide CIs. Conclusions It seemed as though patients with higher MD at baseline were less likely to reach pCR after NACT—a finding more pronounced in premenopausal women. Larger multicenter studies are needed to enable analyses and interpretation for different BC subtypes.

The impact of body size changes on recurrence risk depends on age and estrogen receptor status in primary breast cancer - Helga Tryggvadottir; Maria Ygland Rödström; Andrea Markkula; Xuyian Kenéz; Karolin Isaksson; Signe Borgquist; Helena Jernström (Cancer Causes & Control, 2019)
Purpose To investigate the prognostic impact of body size changes during the first postoperative year in breast cancer. Methods A cohort of 1,317 primary breast cancer patients included in Sweden (2002–2014) underwent body size measurements at the preoperative and 1-year visits ( n = 1,178). Landmark survival analyses were used to investigate how postoperative weight gain or loss (> 5%) or change in waist–hip ratio (WHR) categories (≤ 0.85 or > 0.85) impact prognosis. Results Median age at inclusion was 61 years and body mass index 25.1 kg/m 2 . After a median follow-up of 5.0 years from inclusion, 165 recurrences and 77 deaths occurred. Weight gain (17.0%) conferred over twofold recurrence risk only in patients < 50 years ( P interaction = 0.033). Weight loss (8.6%) was only associated with a poor prognosis in patients ≥ 70 years, but not after restriction analysis. Weight change did not impact prognosis in patients 50 to < 70 years. Changes between WHR categories were associated with differential recurrence risk depending on estrogen receptor (ER) status ( P interaction = 0.007), with higher recurrence risk in patients with ER+ tumors and lower recurrence risk with ER− tumors. Conclusion Both changes in terms of weight and WHR category yielded independent prognostic information. Further research is imperative before recommending weight loss for all overweight breast cancer patients.

Circulating lipids, mammographic density, and risk of breast cancer in the Nurses’ Health Study and Nurses’ Health Study II - Sarah A. Lucht; A. Heather Eliassen; Kimberly A. Bertrand; Thomas P. Ahern; Signe Borgquist; Bernard Rosner; Susan E. Hankinson; Rulla M. Tamimi (Cancer Causes & Control, 2019)

Prospectively measured thyroid hormones and thyroid peroxidase antibodies in relation to risk of different breast cancer subgroups: a Malmö Diet and Cancer Study - Jasmine Brandt; Signe Borgquist; Jonas Manjer (Cancer Causes & Control, 2015)

Mammographic density in relation to tumor biomarkers, molecular subtypes, and mode of detection in breast cancer - Hanna Sartor; Sophia Zackrisson; Karin Elebro; Linda Hartman; Signe Borgquist (Cancer Causes & Control, 2015)

Serum levels of vitamin D, parathyroid hormone and calcium in relation to survival following breast cancer - Linnea Huss; Salma Butt; Signe Borgquist; Martin Almquist; Johan Malm; Jonas Manjer (Cancer Causes & Control, 2014)

Age at first childbirth and oral contraceptive use are associated with risk of androgen receptor-negative breast cancer: the Malmö Diet and Cancer Cohort - Karin Elebro; Salma Butt; Mozhgan Dorkhan; Helena Jernström; Signe Borgquist (Cancer Causes & Control, 2014)

Anthropometric characteristics and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Fatemeh Saberi Hosnijeh; Isabelle Romieu; Valentina Gallo; Elio Riboli; Anne Tjønneland; Jytte Halkjær; Guy Fagherazzi; Françoise Clavel-Chapelon; Laure Dossus; Annie Lukanova; Rudolf Kaaks; Antonia Trichopoulou; et al. (Cancer Causes & Control, 2013)

Exposure to environmental tobacco smoke in childhood and incidence of cancer in adulthood in never smokers in the European prospective investigation into cancer and nutrition - Shu-Chun Chuang; Valentina Gallo; Dominique Michaud; Kim Overvad; Anne Tjønneland; Francoise Clavel-Chapelon; Isabelle Romieu; Kurt Straif; Domenico Palli; Valeria Pala; Rosario Tumino; Carlotta Sacerdote; et al. (Cancer Causes & Control, 2011)